The management of accounting firms: time as an object of professional and commercial goals. Issue 1 (3rd April 2020) - Loscher, Georg Josef; Kaiser, Stephan
Abstract : Purpose: This study aims to explore how commercial and professional management instruments are combined in accounting firms. Design/methodology/approach: The authors conducted a qualitative study based on 30 semi-structured interviews with partners from 30 different accounting firms (sole practitioners to Big Four) in Germany. The study mainly draws from the literature on the management of accounting firms. Findings: The findings of this study indicate that professional and commercial management instruments structure the use of time by accountants. In these management instruments, professional and commercial goals are interwoven by three mechanisms revealed in this study and named as ambivalence, assimilation and integration. The authors further identify the managerial aspects of professional instruments. Originality/value: This paper offers three mechanisms that combine commercial and professional goals in the management of accounting firms. The authors thereby contribute to the literature on the management of accounting firms by analysing these mechanisms that enable the pursuit of both goals simultaneously. Further, the authors argue that the minimum organisation, defined by regulators, of accounting firms is an essential infrastructure for the commercialisation of accounting.